2016
DOI: 10.17586/2220-8054-2016-7-6-911-918
|View full text |Cite
|
Sign up to set email alerts
|

The anisotropic properties of a terbium-based liquid crystal complex

Abstract: The dielectric properties of a paramagnetic terbium-containing liquid crystal have been studied. The magnitude and the sign of the dielectric of the liquid crystalline complex have been determined. The relaxation processes (modes) characterizing the dispersion of the principal values of the sample's dielectric permittivity has been studied. The relaxation times, activation energy and the dipole moment of the complex could be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Dielectric permittivities of all the samples were, therefore, measured with the applied voltage U = 1 V, which does not exceed the Freedericksz transition threshold. 84 Taking into consideration that the director of LC complexes may be unaligned with the magnetic field, 19 the angular behavior of dielectric permittivity components was studied at the temperature that corresponds to the existence of the nematic mesophase to eliminate a possible experimental error (Figure 10 and Figure S2). The samples were aligned macroscopically by a magnetic field of 5000 Oe.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dielectric permittivities of all the samples were, therefore, measured with the applied voltage U = 1 V, which does not exceed the Freedericksz transition threshold. 84 Taking into consideration that the director of LC complexes may be unaligned with the magnetic field, 19 the angular behavior of dielectric permittivity components was studied at the temperature that corresponds to the existence of the nematic mesophase to eliminate a possible experimental error (Figure 10 and Figure S2). The samples were aligned macroscopically by a magnetic field of 5000 Oe.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For all the samples of the lanthanide complexes, it was found that applied electric voltages below 2.5 V do not make a substantial contribution to their alignment (Figure S1). Dielectric permittivities of all the samples were, therefore, measured with the applied voltage U = 1 V, which does not exceed the Freedericksz transition threshold …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation